Conceptual Aspects of Global Value Chains - Antras, Pol (World Bank, Washington, DC, 2020)
The paper offers an overview of some key conceptual aspects associated with the rise of global value chains (GVCs). It outlines a series of alternative interpretations and definitions of what the rise of GVCs entails, and it traces the implications of these alternative conceptualizations for the measurement of the phenomenon, as well as for elucidating the key determinants and implications of GVC participation, both at the country level and at the firm level. In the process, the paper offers some speculative thoughts about the future of GVCs in light of the advent of an array of new technologies.